The Pentatricopeptide Repeat Protein MEF100 Is Required for the Editing of Four Mitochondrial Editing Sites in Arabidopsis - Bernard Gutmann; Michael Millman; Lilian Vincis Pereira Sanglard; Ian Small; Catherine Colas des Francs-Small (Cells, 2021)
In Arabidopsis thaliana there are more than 600 C-to-U RNA editing events in the mitochondria and at least 44 in the chloroplasts. Pentatricopeptide repeat (PPR) proteins provide the specificity for these reactions. They recognize RNA sequences in a partially predictable fashion via key amino acids at the fifth and last position in each PPR motif that bind to individual ribonucleotides. A combined approach of RNA-Seq, mutant complementation, electrophoresis of mitochondrial protein complexes and Western blotting allowed us to show that MEF100, a PPR protein identified in a genetic screen for mutants resistant to an inhibitor of γ -glutamylcysteine synthetase, is required for the editing of nad1-493, nad4-403, nad7-698 and ccmFN2-356 sites in Arabidopsis mitochondria. The absence of editing in mef100 leads to a decrease in mitochondrial Complex I activity, which probably explains the physiological phenotype. Some plants have lost the requirement for MEF100 at one or more of these sites through mutations in the mitochondrial genome. We show that loss of the requirement for MEF100 editing leads to divergence in the MEF100 binding site.